2016
DOI: 10.22160/22035184/aras-2016-37-2/56-79
|View full text |Cite
|
Sign up to set email alerts
|

News Media Reporting on Substance Use Among People of African Ethnicity in Three Australian States, 2003-2013

Abstract: The media play an important role in influencing public opinion and community discourse about health issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…This fits under the “safety and stability” domain and includes representations in the news, political speeches, talkback radio, letters to the editor, and so on. There is significant research on this in Australia (Budarick & Han, 2015; Han & Budarick, 2018; Hanson‐Easey et al, 2014; Horyniak et al, 2016; MacDonald, 2017; Nolan et al, 2018; Phillips, 2011; Windle, 2008). It indicates that negative news reporting impacts African migrants, from interactions with police, to employment opportunities, to reinforcing the negativity of the general population.…”
Section: African Migrants and Integration In Australia – An Analysis ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This fits under the “safety and stability” domain and includes representations in the news, political speeches, talkback radio, letters to the editor, and so on. There is significant research on this in Australia (Budarick & Han, 2015; Han & Budarick, 2018; Hanson‐Easey et al, 2014; Horyniak et al, 2016; MacDonald, 2017; Nolan et al, 2018; Phillips, 2011; Windle, 2008). It indicates that negative news reporting impacts African migrants, from interactions with police, to employment opportunities, to reinforcing the negativity of the general population.…”
Section: African Migrants and Integration In Australia – An Analysis ...mentioning
confidence: 99%
“…MacDonald (2017) explains this in terms of spatial, relational and socio‐political exclusion. As noted, print media reporting of young people of African refugee backgrounds focuses on crime, violence, and substance use (Horyniak et al, 2016). However, on the positive side, African “ethnic minority” or “community” media is rapidly developing, focused on communicating within and across communities and seeking to positively affect the practices and understandings of the wider Australian community and journalists through the dissemination of positive stories (Budarick & Han, 2015; Han & Budarick, 2018; Hebbani & van Vuuren, 2015).…”
Section: African Migrants and Integration In Australia – An Analysis ...mentioning
confidence: 99%
“…They found that newspaper reports have become more disapproving in nature with a focus on restrictions, trauma, prevention and drink driving. In a more targeted study focusing on the media reporting on AOD use among people of African ethnicity, Horyniak et al [11] found that alcohol‐related stories were the most common (68%) and often related to violence (47%) and crime (32%).…”
Section: Introductionmentioning
confidence: 99%